2016
DOI: 10.1177/0269215515625100
|View full text |Cite
|
Sign up to set email alerts
|

Improving practice with integration of patient directed activity during inpatient rehabilitation

Abstract: The "Patient Directed Activity Program" includes distinct activity stations designed to increase repetition, stimulation, attention, and activity of the affected upper extremities, lower extremities, and trunk. Each task-specific activity was easily graded to achieve moderate- to high-intensity. The activity program prescribed individuals up to three additional 30-minute bouts of activities daily that were to be completed independently, and in addition to standard of care. Clinical application: After implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…The study purpose was to examine the impact of a patient-directed activity program 15 to increase functional outcomes and activity participation after stroke. The additional functional activity via Patient-Directed Activity Program had limited impact on our patients' outcomes beyond those achieved by patients receiving usual care only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study purpose was to examine the impact of a patient-directed activity program 15 to increase functional outcomes and activity participation after stroke. The additional functional activity via Patient-Directed Activity Program had limited impact on our patients' outcomes beyond those achieved by patients receiving usual care only.…”
Section: Discussionmentioning
confidence: 99%
“…Baylor Scott & White Institute for Rehabilitation provided oversight for the integrity and conduct of this study as described in our previous paper published in Clinical Rehabilitation. 15 Baylor Scott & White Institute for Rehabilitation is a large free-standing inpatient rehabilitation hospital connected to a level 1 trauma acute care hospital.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in Australia 37 concluded that dose-driven interventions, including circuit class therapy and 7-days-a-week therapy, increased the amounts of therapy provided but did not increase meaningful patient activity outside therapy sessions; the researchers called for greater understanding of the drivers of activity outside therapy sessions. Trammell et al 38 found that a programme of physical activities 'prescribed' in addition to structured therapy on a stroke unit was feasible, but again this was overseen and graded by therapists. Although the research team found that staff and patients reported high satisfaction, levels of expectations about activity prior to implementation were not known and the activities consisted of repetitive exercises that required supervision.…”
Section: Rehabilitation Recovery and Persistent Concernsmentioning
confidence: 99%
“…A total of 712 titles and abstracts were identified for screening; of these, 24 papers went forward for full-text review. Eleven publications 18,[30][31][32][33][34][35][36][37][38][39][40] were included in the final evidence synthesis (see Report Supplementary Material 5 for the PRISMA flow diagram and checklist).…”
Section: Rapid Evidence Synthesis (Objective 1)mentioning
confidence: 99%